Characterization of the Interaction of Nerve Agent Mimics with Selected Synthetic Receptors - Braga Barbosa, Carolina; Gaß, Patrick; Hamsch, Daniel J.; Kubik, Stefan (Organic Materials, 2022)
Qualitative NMR spectroscopic and quantitative calorimetric binding studies were performed to characterize the interaction of nontoxic mimics of the V-type nerve agent VX (O-ethyl S-[2-(diisopropylamino)ethyl] methylphosphonothioate) and the Novichok nerve agent A-234 (ethyl (1-(diethylamino)ethylidene)phosphoramidofluoridate) with a series of receptors in 100 mM aqueous phosphate buffer at pH 7.4 and 37 °C. These investigations provided information about the preferred geometry with which the nerve agent mimics are included into the receptor cavities and about the stability of the complexes formed. According to the results, the positively charged VX mimic prefers to bind to cation receptors such as sulfonated calixarenes and an acyclic cucurbituril but does not noticeably interact with cyclodextrins. While binding to the acyclic cucurbituril is stronger than that to calixarenes, the mode of inclusion into the sulfonatocalix[4]arene cavity is better suited for the development of scavengers that bind and detoxify V-type nerve agents. The neutral Novichok mimic, on the other hand, only interacts with the acyclic cucurbituril with a strength required for scavenger development. These binding studies thus provided guidelines for the further development of nerve agent scavengers.
Keywords: nerve agents; sulfonatocalixarenes; cyclodextrins; acyclic cucurbiturils; binding studies